Audiograms and click spectra of seven novel and seldom-tested odontocetes - Houser, Dorian S.; Noble, Lauren; Fougeres, Erin; Mulsow, Jason; Finneran, James J. (Frontiers in Marine Science, 2022)
The use of auditory evoked potentials has been promoted as a means by which to collect audiometric information from odontocete cetaceans that are rarely encountered in stranding situations. This article presents the results of auditory evoked potential hearing tests collected from stranded odontocetes over nearly a decade. For six species, no audiograms previously existed – the dwarf sperm whale (Kogia sima), pygmy sperm whale (Kogia breviceps), northern right whale dolphin (Lissodelphis borealis), melon-headed whale (Peponocephala electra), long-beaked common dolphin (Delphinus capensis), and Atlantic spotted dolphin (Stenella frontalis). Additional hearing information was gathered for the pygmy killer whale (Feresa attenuata), a species for which only two prior audiograms had been collected. Audiograms for the delphinids demonstrated a typical dolphin-like form with upper-frequency limits of hearing > 149 kHz, except for the pygmy killer whales whose upper-frequency limit was between 103-107 kHz. The kogiid audiograms had a narrower region of increased sensitivity (80-128 kHz) closely aligned with their narrowband, high-frequency echolocation signals. Distinctions between kogiids and delphinids existed in the latencies of peaks of click-evoked auditory brainstem responses, with longer interwave intervals between P4 and N5 in the kogiids (mean of 0.60 ms vs. a mean of 0.37 ms in the delphinids). Modulation rate transfer functions collected in three of the species, suggested group-wide similarities in temporal processing capabilities.